Measurement of f1(1285) production in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Physics letters, 2025)
This study presents the first measurement of the f1(1285) resonance using the ALICE detector in inelastic proton-proton collisions at a center-of-mass energy of 13 TeV. The resonance is reconstructed at midrapidity (|y|< 0.5) through the hadronic decay channel f1(1285)→KS0K±π∓. Key measurements include the determination of its mass, transverse-momentum integrated yield, and average transverse momentum. Additionally, the ratio of the transverse-momentum integrated yield of f1(1285) to pion is compared with calculations from the canonical statistical hadronization model. The model calculation, assuming a zero total strangeness content for f1(1285), reproduces the data within 1σ deviation, shedding light on the quark composition of f1(1285).
Online verfügbar: 16. Mai 2025, Artikelversion: 21. Mai 2025
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grundwald, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F Stiefelmaier, C.A. van Veen, B. Windelband, A. Yuncu, F. Zanone, B. Zhang [und 1056 weitere Personen]
Gesehen am 14.11.2025
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Im Titel ist die Zahl 1 tiefgestellt